NOISE AND SUBJECTIVE COMPLAINTS OF WORKERS AS EFFORT TO CONTROL THE OCCURRENCE OF NOISE INDUCED PERMANENT THRESHOLD SHIF (NIPTS) - Wardani, Ratnaningtyas Wahyu Kusuma; Nurika, Globila; Lutfiya, Indah; Nawawinetu, Erwin Dyah (Journal of Vocational Health Studies, 2020)
Background: Timber industry is one industry that has experienced an increase in noise levels as a result of the presence of modern machines, higher speeds, and more levels so that the risk of workers experiencing hearing loss due to noise can increase as the occurrence of Noise-Induced Permanent Threshold Shif (NIPTS). Purpose: The purpose of this study is to analyze the risk factors associated with subjective complaints of workers due to noise at work and formulate control measures to prevent the occurrence of NIPTS. Method: This type of research is analytic observational with a cross-sectional design at PT.X, Probolinggo Regency in June 2019. The research sample of 44 respondents was chosen randomly by simple random sampling and the data were analyzed by chi-square test (α = 0.05). Result: The results of noise measurements in the work environment show that the 5 areas in the production section, only 3 areas have an average noise more than 85 dBA, namely WW1, WW2, and WW3. Whereas the most non-auditory complaints suffered by workers were among those with noise intensity of more than 85 dBA and in the WW2 and WW1 work areas. The results of cross-tabulation and analysis of Chi-Square statistical tests showed that the value of p = 0,000 <(α = 0.05). This means there is a significant relationship between noise intensity with complaints of hearing loss in workers. Conclusion: only the intensity of noise with complaints of hearing loss in workers who have a statistically significant relationship.